Composite binder and preparation method thereof, electrode plate and secondary battery

By using the preparation method of composite adhesive in the preparation of dry electrode sheets, the cocondensation reaction of colloidal fluoropolymer and dopamine is used to solve the problems of insufficient bonding strength of the existing adhesive and poor wetting of the electrolyte, and higher bonding strength, electrolyte wetting and stability are achieved, and the overall performance of the battery is improved.

CN119614103APending Publication Date: 2025-03-14SHENZHEN QINGYAN ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411906057.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The binder in the preparation of existing dry electrode sheets, such as polytetrafluoroethylene, has problems such as insufficient bonding force and hindering the wettability of the electrolyte.

Method used

By using the preparation method of composite binder, a co-coagulated reaction is carried out by mixing a colloidal fluoropolymer with a solution of a catechol-containing substance (such as dopamine) to form a composite binder with improved properties.

Benefits of technology

It improves the adhesive force, electrolyte wetting and stability, enhances the compatibility between the electrode sheet and the electrolyte, reduces the interface resistance of the electrode sheet, and improves the rate performance, capacity performance and cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614103A_ABST
    Figure CN119614103A_ABST
Patent Text Reader

Abstract

The invention relates to a composite binder and a preparation method thereof, an electrode plate and a secondary battery, and the preparation method of the composite binder comprises the following steps: providing a colloidal fluorine-containing polymer which comprises one or more of a homopolymer, a copolymer and a terpolymer formed by polymerization units, the polymerization unit comprises one or more of tetrafluoroethylene, chlorotrifluoroethylene, perfluoroalkyl vinyl ether and hexafluoropropylene; a solution of a substance containing a catechol structure is provided, the substance containing the catechol structure comprises one or more of dopamine, epicatechin, epicatechin gallate, epigalloyl catechin, epigalloyl catechin gallate and derivatives of the dopamine, the epicatechin, the epicatechin gallate, the epigalloyl catechin gallate and the derivatives of the dopamine, the epicatechin, the epicatechin gallate, the epigalloyl catechin gallate and the derivatives of the epigalloyl catechin gallate, and the solution is alkaline; the method comprises the following steps: mixing a colloidal fluorine-containing polymer with a solution of a substance containing a catechol structure to obtain a mixed solution, reacting the mixed solution under a dark condition, co-condensing the reacted solution to obtain a precipitate, floating the precipitate on the surface of the solution, and containing the composite binder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrode sheet preparation, and in particular to a composite binder and a preparation method thereof, an electrode sheet and a secondary battery. Background Art

[0002] The preparation of dry-process electrodes includes adding a binder to the electrode film powder (including active material powder and conductive agent). Under the action of external shear force, the binder undergoes fibrillation, adheres to the electrode film powder, and forms a self-supporting film after extrusion and covers the surface of the current collector. However, the commonly used binders, such as polytetrafluoroethylene (PTFE), have the defect of insufficient bonding force, and PTFE is a hydrophobic polymer, which has caused certain obstacles to the electrode infiltration of the electrolyte. Summary of the invention

[0003] In view of this, the present application provides a composite adhesive and a preparation method thereof to solve at least one of the above problems.

[0004] To achieve the above-mentioned purpose, in a first aspect, the present application provides a method for preparing a composite binder, comprising: providing a colloidal fluorine-containing polymer, wherein the fluorine-containing polymer comprises one or more of a homopolymer, a copolymer and a terpolymer formed by polymerization units, wherein the polymerization units comprise one or more of tetrafluoroethylene, chlorotrifluoroethylene, perfluoroalkyl vinyl ether and hexafluoropropylene; providing a solution of a substance containing a catechol structure, wherein the substance containing a catechol structure comprises one or more of dopamine, epicatechin, epicatechin gallate, epigallocatechin, epigallocatechin gallate, and derivatives thereof, wherein the solution is alkaline; mixing the colloidal fluorine-containing polymer with the solution of the substance containing a catechol structure to obtain a mixed solution, reacting the mixed solution under light-proof conditions, and co-coagulating the solution after the reaction to obtain a precipitate, wherein the precipitate floats on the surface of the solution, and the precipitate contains the composite binder.

[0005] In some possible implementations, the particle size of the colloidal fluorine-containing polymer is 300 nm to 500 nm.

[0006] In some possible implementations, the molecular weight of the fluorine-containing polymer is 10,000 Da to 1,000,000 Da.

[0007] In some possible implementations, the preparation method further includes filtering and drying the precipitate to obtain the composite binder.

[0008] In some possible implementations, the co-coagulation is performed under stirring.

[0009] In some possible implementations, the co-coagulation is performed at an alkaline pH.

[0010] In some possible implementations, the co-coagulation is performed under the addition of ethanol.

[0011] In some possible implementations, the reaction time of the mixed solution is 6 h to 48 h.

[0012] In some possible implementations, the mixed solution reaction is carried out under stirring.

[0013] In some possible implementations, providing a solution of a substance containing a catechol structure includes mixing the substance containing a catechol structure with a solvent, wherein the solvent includes one or more of a tris(hydroxymethyl)aminomethane hydrochloride solution, a phosphate solution, and a hydroxyethylpiperazine ethanesulfonic acid solution, to obtain a solution of the substance containing a catechol structure, wherein the concentration of the solution is 1 mg / mL to 100 mg / mL.

[0014] In the preparation method provided in the first aspect above, the substance containing catechol structure (such as dopamine) undergoes self-polymerization reaction in an alkaline environment to form long chains, and some colloidal particles adsorb the long chains, so that these colloidal particles can be linked by long chain bridges, or dopamine molecules are attached to the surface of some colloidal particles, and dopamine is attached to the surface of the colloidal particles after self-polymerization. In this application, due to the use of colloidal fluorinated polymers, the reactants in the mixed solution can be precipitated through co-coagulation. In particular, after co-coagulation, the precipitate floats on the surface of the mixed solution, and the precipitate can obtain a final product with better performance improvement. Since dopamine forms -OH and -NH groups after self-polymerization, it is beneficial to improve the electrolyte wettability of the fluorinated polymer. Moreover, dopamine forms long chains after self-polymerization and entangles with colloidal particles, which is beneficial to increase the adhesion of the fluorinated polymer. In addition, after self-polymerization, it is attached to the surface of the fluorinated polymer, which can reduce the phenomenon of fibrosis of the fluorinated polymer at room temperature, which is beneficial to improve the stability of the fluorinated polymer at room temperature, and is beneficial to better control the fibrosis of the fluorinated polymer under specific conditions.

[0015] In a second aspect, the present application provides a composite adhesive prepared by the above-mentioned preparation method.

[0016] The composite adhesive of the present application is obtained by co-coagulation of a fluorinated polymer colloid and a substance containing a catechol structure after reaction. The substance containing a catechol structure (such as dopamine) has -OH and -NH groups after self-polymerization, which is beneficial to improving the electrolyte wettability of the fluorinated polymer. Moreover, after self-polymerization, dopamine forms long chains that are entangled with the colloidal particles, which is beneficial to increasing the adhesion of the fluorinated polymer. In addition, after self-polymerization, dopamine adheres to the surface of the fluorinated polymer, which can reduce the phenomenon of fibrosis of the fluorinated polymer at room temperature, which is beneficial to improving the stability of the fluorinated polymer at room temperature. Therefore, the composite adhesive of the present application has improved adhesion, electrolyte wettability and stability.

[0017] In a third aspect, the present application provides an electrode sheet, comprising a current collector and an electrode coating provided on at least one surface of the current collector, wherein the electrode coating comprises an active material, a conductive agent and a binder, and the binder comprises the above-mentioned composite binder.

[0018] In the electrode sheet of the present application, the binder contains the above-mentioned composite binder, so that the material of the electrode coating can be better bonded, and the electrode sheet has good wettability with the electrolyte, which is beneficial to reducing the interface resistance of the electrode sheet and shortening the ion transmission path, which is beneficial to provide the battery with better rate performance, capacity utilization and cycle life.

[0019] In a fourth aspect, the present application provides a secondary battery comprising the above-mentioned electrode sheet.

[0020] The secondary battery of the present application has low internal resistance, high ion transmission efficiency, and good rate performance, capacity and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A flow chart of a method for preparing a composite adhesive provided in one embodiment of the present application.

[0022] Figure 2 This is a scanning electron microscope image of the composite binder particles provided in Example 1 of the present application.

[0023] Figure 3 This is a scanning electron microscope image of the composite binder particles provided in Comparative Example 1 of the present application.

[0024] Figure 4 Infrared analysis spectra of the composite adhesive provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0025] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0026] Based on this, an embodiment of the present application provides a method for preparing a composite adhesive, please refer to Figure 1 , the preparation method comprises: S100: providing a colloidal fluorine-containing polymer, wherein the fluorine-containing polymer comprises one or more of a homopolymer, a copolymer and a terpolymer formed by polymerization units, wherein the polymerization units comprise one or more of tetrafluoroethylene, chlorotrifluoroethylene, perfluoroalkyl vinyl ether and hexafluoropropylene.

[0027] Homopolymers, copolymers or terpolymers containing the above substances as polymerization units are often used as binders in the field of batteries. They are added to electrode film powders (including active material powders and conductive agents), and the electrode film powders are bonded through fibrillation. They are then extruded to form a self-supporting film and covered on the surface of the current collector. This application selects such fluorinated polymers in colloidal form as one of the raw materials for the composite binder, which is different from other physical states of the same substance (powder, solution, etc.). Taking polytetrafluoroethylene (homopolymer with tetrafluoroethylene as a polymerization unit) as an example, compared with polytetrafluoroethylene powder, polytetrafluoroethylene colloid combined with the reactants and reaction conditions involved in the subsequent steps can obtain a final product with better performance improvement.

[0028] In some embodiments, the particle size of the colloidal fluoropolymer is 300 nm to 500 nm. For example, the particle size of the colloidal fluoropolymer can be 300 nm, 320 nm, 340 nm, 360 nm, 380 nm, 400 nm, 420 nm, 440 nm, 460 nm, 480 nm, 500 nm or any value within the range formed by any two of the above values. It is understandable that the particle size of the fluoropolymer particles in other physical states (powder, solution) is different from that of the colloidal fluoropolymer, and it is generally believed that the particle size of the powdered fluoropolymer is larger than that of the colloidal fluoropolymer. The present application is prepared by modifying the colloidal fluoropolymer in the above-mentioned particle size range, which is conducive to making the obtained composite binder have better performance.

[0029] In some embodiments, the molecular weight of the fluoropolymer is 10000 Da to 1000000 Da. For example, the molecular weight of the fluoropolymer can be 10000 Da, 30000 Da, 50000 Da, 70000 Da, 100000 Da, 300000 Da, 500000 Da, 700000 Da, 1000000 Da, or any value within the range formed by any two of the above values. The colloid adhesion formed by the fluoropolymer with the above molecular weight is greater and the mechanical strength is also greater. From the perspective of improving mechanical strength, the molecular weight of the fluoropolymer can be further preferably 100000 Da to 1000000 Da.

[0030] S200: providing a solution of a substance containing a catechol structure, wherein the substance containing a catechol structure comprises one or more of dopamine, epicatechin, epicatechin gallate, epigallocatechin, epigallocatechin gallate, and derivatives thereof, and the solution is alkaline.

[0031] Taking dopamine as an example, dopamine can undergo self-polymerization in an alkaline solution to form long chains, and after self-polymerization, -OH and -NH functional groups are formed, and the hydrophilicity is good. Preferably, the solution pH is 8 to 10.

[0032] In some embodiments, S200 may be implemented by S201 .

[0033] S201: Mixing the substance containing the catechol structure with a solvent, wherein the solvent includes one or more of a tris(hydroxymethyl)aminomethane hydrochloride solution, a phosphate solution, and a hydroxyethylpiperazine ethanesulfonic acid solution, to obtain a solution of the substance containing the catechol structure, wherein the concentration of the solution is 1 mg / mL to 100 mg / mL. For example, the concentration of the solution can be 1 mg / mL, 5 mg / mL, 10 mg / mL, 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, 60 mg / mL, 70 mg / mL, 80 mg / mL, 90 mg / mL, 100 mg / mL, or any value within the range formed by any two of the above values.

[0034] S300: mixing the colloidal fluorine-containing polymer with the solution of the substance containing the catechol structure to obtain a mixed solution, reacting the mixed solution under light-proof conditions, and co-coagulating the solution after the reaction to obtain a precipitate, wherein the precipitate floats on the surface of the solution and contains the composite binder.

[0035] In this process, the colloidal fluorinated polymer in the mixed liquid is mixed with the substance containing the catechol structure and reacted under preset conditions. The substance containing the catechol structure (such as dopamine) undergoes self-polymerization reaction in an alkaline environment to form long chains, and some colloidal particles adsorb the long chains, so that these colloidal particles can be linked by long chain bridges, or dopamine molecules are attached to the surface of some colloidal particles, and dopamine is attached to the surface of the colloidal particles after self-polymerization. In this application, due to the use of colloidal fluorinated polymers, the reactants in the mixed liquid can be precipitated through co-coagulation. In particular, after co-coagulation, the precipitate floats on the surface of the mixed liquid, and the precipitate can obtain a final product with better performance improvement.

[0036] Since dopamine forms -OH and -NH groups after self-polymerization, it is beneficial to improve the electrolyte wettability of fluoropolymers. Moreover, dopamine forms long chains after self-polymerization and entangles with colloidal particles, which is beneficial to increase the adhesion of fluoropolymers. In addition, fluoropolymers (such as polytetrafluoroethylene) have multiple crystal phase structures. Below 19 ° C, they are mainly hexagonal crystals, which are easy to fiberize and transform into pseudo-hexagonal crystals, resulting in their unstable structure at room temperature. Dopamine adheres to the surface of fluoropolymers after self-polymerization, which can reduce the fiberization of fluoropolymers at room temperature. At the same time, it does not change the crystal form of fluoropolymers, which is beneficial to improve the stability of fluoropolymers at room temperature and better control the fiberization of fluoropolymers under specific conditions.

[0037] In some embodiments, the co-coagulation is carried out under stirring, preferably, the stirring rate is 50 rpm to 150 rpm, for example, it can be 50 rpm, 70 rpm, 90 rpm, 110 rpm, 130 rpm, 150 rpm or any value within the range formed by any two of the above values. In some embodiments, the co-coagulation is carried out under alkaline pH, preferably, the pH is 8 to 10, for example, it can be 8, 8.2, 8.5, 8.7, 9, 9.2, 9.5, 9.7, 10 or any value within the range formed by any two of the above values. In some embodiments, the co-coagulation is carried out under the addition of ethanol. Providing the above conditions can further promote the occurrence of the above co-coagulation, so that the reactants in the mixed solution are precipitated and float on the surface of the mixed solution.

[0038] In some embodiments, the reaction time of the mixed solution is 6 h to 48 h. For example, the reaction time of the mixed solution can be 6 h, 8 h, 12 h, 16 h, 22 h, 28 h, 36 h, 42 h, 48 h, or any value within the range formed by any two of the above values. Controlling the reaction time of the mixed solution within the above range is conducive to fully proceeding the reaction, promoting the interaction between the products, and improving the degree of improvement of the performance of the final product.

[0039] In some embodiments, the mixed solution reaction is carried out under stirring. Stirring can promote the mixed solution to be fully mixed, which is conducive to the full progress of the reaction and can also avoid excessive coagulation of the product.

[0040] In some embodiments, the preparation method further includes S310.

[0041] S310: filtering and drying the precipitate to obtain the composite binder.

[0042] An embodiment of the present application further provides a composite adhesive prepared by the above-mentioned preparation method.

[0043] The composite adhesive of the present application is obtained by co-coagulation of a fluorinated polymer colloid and a substance containing a catechol structure after reaction. The substance containing a catechol structure (such as dopamine) has -OH and -NH groups after self-polymerization, which is beneficial to improving the electrolyte wettability of the fluorinated polymer. Moreover, after self-polymerization, dopamine forms long chains that are entangled with the colloidal particles, which is beneficial to increasing the adhesion of the fluorinated polymer. In addition, after self-polymerization, dopamine adheres to the surface of the fluorinated polymer, which can reduce the phenomenon of fibrosis of the fluorinated polymer at room temperature, which is beneficial to improving the stability of the fluorinated polymer at room temperature. Therefore, the composite adhesive of the present application has improved adhesion, electrolyte wettability and stability.

[0044] An embodiment of the present application further provides an electrode sheet, comprising a current collector and an electrode coating disposed on at least one surface of the current collector, wherein the electrode coating comprises an active material, a conductive agent and a binder, and the binder comprises the above-mentioned composite binder.

[0045] In the electrode sheet of the present application, the binder contains the above-mentioned composite binder, so that the material of the electrode coating can be better bonded, and the electrode sheet has good wettability with the electrolyte, which is beneficial to reducing the interface resistance of the electrode sheet and shortening the ion transmission path, which is beneficial to provide the battery with better rate performance, capacity utilization and cycle life.

[0046] An embodiment of the present application further provides a secondary battery, comprising the above-mentioned electrode sheet.

[0047] The secondary battery of the present application has low internal resistance, high ion transmission efficiency, and good rate performance, capacity and cycle life.

[0048] The scheme of the present application will be explained below in conjunction with the embodiments. Those skilled in the art will understand that the following examples are only used to explain the present application and cannot be construed as limiting the present application. Unless otherwise stated, the reagents, software and instruments not specifically stated in the following embodiments are all conventional commercial products or open source.

[0049] Embodiment 1: A composite adhesive, the preparation method comprising: Step 1: Dissolve 121 g of Tris-HCl powder in 600 mL of ultrapure water, adjust the solution pH to 8.5 with concentrated hydrochloric acid or sodium hydroxide, and add ultrapure water to make up to 1 L.

[0050] Step 2, add 0.16 g of dopamine hydrochloride to Tris-HCl solution (PH=8.5) to prepare a dopamine solution with a concentration of 16 mg / mL.

[0051] Step 3, under stirring at 300 rpm, add polytetrafluoroethylene emulsion (molecular weight 500000 Da) dropwise into the dopamine solution of step 2, mix evenly, react under stirring and light-proof conditions, maintain stirring at 50 rpm to 150 rpm, and co-coagulation occurs to form precipitated particles, and the precipitated particles float on the surface of the mixed solution.

[0052] Step 4, filtering the mixed solution obtained in step 3, washing the filter residue with deionized water for 3 to 5 times, and then vacuum drying for 48 hours to obtain a composite binder.

[0053] Embodiment 2: The difference from Example 1 is that in step 1, polytetrafluoroethylene is replaced with one having a molecular weight of 1,000,000 Da.

[0054] Embodiment 3: The difference from Example 1 is that in step 2, the concentration of dopamine hydrochloride is 2 mg / mL.

[0055] Comparative Example 1: The difference from Example 1 is that in step 2, no dopamine solution is added and the PTFE solution is co-coagulated.

[0056] Comparative Example 2: The difference from Example 1 is that in step 3, the polytetrafluoroethylene powder particles are mixed with the dopamine solution of step 2, and reacted under stirring and light-proof conditions to obtain a mixed solution.

[0057] The composite binder obtained in the above-mentioned Examples 1-3 and Comparative Examples 1-2 is used to prepare an electrode sheet, and the specific steps include: weighing 94 wt% of the active material NCM, 4 wt% of the composite binder and 2 wt% of the conductive carbon black, and fully mixing these materials in a high-speed mixer to ensure that the composite binder, the conductive carbon black and the active material are evenly dispersed and mixed. Then, the mixed powder is hot-rolled into a film with a thickness of 120 μm, and then the film is thermally composited with the current collector to obtain an electrode sheet.

[0058] The present application also conducted a morphology test on the above electrode sheet, and the test method and test results are as follows: 1. Electron microscopy test of powder in electrode sheet: Use gold sputtering instrument (JY-S100 PLUS) to spray gold on the powder in electrode sheet, and then use electron microscopy tester (Phenom XL0027-L) to carry out electron microscopy test.

[0059] 2. Infrared test of powder in electrode sheet: Use Thermo Fisher Scientific Fourier Transform Infrared Spectrometer is50 for infrared test.

[0060] See also Figure 2 and Figure 3 , Figure 2 The composite adhesive of Example 1 has a dense coating on its surface, which is a PDA polymer. Figure 3 The adhesive surface of Comparative Example 1 has no PDA coating. This indicates that a composite adhesive having polydopamine attached to the surface of a fluorine-containing polymer can be prepared by mixing the fluorine-containing polymer with dopamine according to the preparation method of the present application.

[0061] See also Figure 4 Compared with Comparative Example 1, the composite binder of Example 1 has a -1 There is a NH symmetric characteristic absorption peak at 1555 cm -1 The characteristic absorption peak of the aromatic ring in polydopamine appears at , indicating that the composite binder of Example 1 contains -NH groups and polydopamine.

[0062] The present application also conducted a performance test on the above electrode sheet, and the test method and test results are as follows: 1. Mechanical property test of the membrane in the electrode sheet: The prepared ternary membrane was cut into strips with a width of 20 cm and a length of 120 cm, and then the tensile performance test was carried out according to the test method of the national standard "GB / T16491-2008". The test instrument was an MTS universal testing machine.

[0063] 2. Electrode sheet volume resistance test: Use Japanese HIOKI-LCR tester IM3536 for testing, place the electrode sheet at the intersection, input the thickness of the current collector and the thickness of the membrane, and then test.

[0064] 3. Electrolyte wettability test of electrode sheet: Cut the electrode sheet into small discs with a diameter of 14 mm, and then use the contact angle tester (HARKE-SPC) to test the electrolyte contact angle. The contact angle refers to the angle θe between the tangent of the gas-liquid interface and the solid-liquid boundary line at the intersection of the gas, liquid and solid phases, which is a measure of the degree of wettability. If θe<90°, the solid is lyophilic, that is, the liquid can wet the solid, and the smaller the angle, the better the wettability; if θe>90°, the solid is hydrophobic, that is, the liquid does not wet the solid and is easy to move on the surface.

[0065] Please refer to Table 1 for the above test results.

[0066] Table 1. Performance test results of the electrode sheets of Examples 1-3 and Comparative Examples 1-2 of the present application As can be seen from Table 1, Examples 1-3 use colloidal fluorinated polymers and dopamine as raw materials, and a composite binder is prepared by the preparation method of the present application. The composite binder has improved electrolyte wettability and adhesion and higher stability, so that the membrane using the composite binder has higher tensile strength, and the electrode sheet using the composite binder has better electrolyte wettability and lower interface resistance, which is beneficial to shortening the ion transmission path and providing the battery with better rate performance, capacity utilization and cycle life.

[0067] Compared with Example 1, dopamine was not added to the raw materials of Comparative Example 1, and the tensile strength of the corresponding diaphragm was significantly reduced, there was a problem of insufficient bonding, and the electrolyte wettability and interface resistance of the electrode sheet were not significantly improved.

[0068] Compared with Example 1, the raw materials of Comparative Example 2 use polytetrafluoroethylene powder particles instead of polytetrafluoroethylene colloid. The particle size of the polytetrafluoroethylene powder particles is relatively large, and it is simply blended with dopamine. Due to the difference in physical states (powder particles and colloid), the composite binder of Comparative Example 2 is obtained without co-coagulation. After testing, the tensile strength of the corresponding diaphragm is significantly lower than that of the embodiments of the present application, and the electrolyte wettability of the electrode sheet is still poor, and the interface resistance is high.

[0069] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application has been described in detail with reference to the above preferred implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.

Claims

1. A method for preparing a composite adhesive, characterized in that: The preparation method comprises: Providing a colloidal fluorine-containing polymer, the fluorine-containing polymer comprising one or more of a homopolymer, a copolymer and a terpolymer formed by polymerized units, the polymerized units comprising one or more of tetrafluoroethylene, chlorotrifluoroethylene, perfluoroalkyl vinyl ether and hexafluoropropylene; Providing a solution of a substance containing a catechol structure, wherein the substance containing a catechol structure comprises one or more of dopamine, epicatechin, epicatechin gallate, epigallocatechin, epigallocatechin gallate, and derivatives thereof, wherein the solution is alkaline; The colloidal fluorine-containing polymer is mixed with a solution of the substance containing a catechol structure to obtain a mixed solution. The mixed solution is reacted under light-proof conditions to co-coagulate the reacted solution to obtain a precipitate. The precipitate floats on the surface of the mixed solution and contains the composite binder.

2. The preparation method according to claim 1, characterized in that The particle size of the colloidal fluorine-containing polymer is 300 nm to 500 nm.

3. The preparation method according to claim 1, characterized in that The molecular weight of the fluorine-containing polymer is 10,000 Da to 1,000,000 Da.

4. The preparation method according to claim 1, characterized in that: The preparation method further comprises filtering and drying the precipitate to obtain the composite binder.

5. The preparation method according to claim 1, characterized in that: The co-coagulation satisfies at least one of the following conditions: (1) The co-coagulation is carried out under stirring; (2) the co-coagulation is carried out at an alkaline pH; (3) The co-coagulation is carried out under the addition of ethanol.

6. The preparation method according to claim 1, characterized in that: The mixed solution reaction satisfies at least one of the following conditions: (1) The reaction time of the mixed solution is 6 h to 48 h; (2) The mixed solution reaction is carried out under stirring.

7. The preparation method according to claim 1, characterized in that The method of providing a solution of a substance containing a catechol structure comprises mixing the substance containing a catechol structure with a solvent, wherein the solvent comprises one or more of a tris(hydroxymethyl)aminomethane hydrochloride solution, a phosphate solution, and a hydroxyethylpiperazine ethanesulfonic acid solution, to obtain a solution of the substance containing a catechol structure, wherein the concentration of the solution is 1 mg / mL to 100 mg / mL.

8. A composite adhesive, characterized in that: The composite binder is prepared by the preparation method according to any one of claims 1 to 7.

9. An electrode sheet, comprising a current collector and an electrode coating disposed on at least one surface of the current collector, wherein the electrode coating comprises an active material, a conductive agent and a binder, wherein: The adhesive comprises the composite adhesive as claimed in claim 8.

10. A secondary battery, characterized in that: Comprising the electrode sheet as claimed in claim 9.

Citation Information

Cited By

  • Composite binder and preparation method thereof, pole piece and battery

    CN121379418A